2017
DOI: 10.1186/s12931-017-0648-0
|View full text |Cite
|
Sign up to set email alerts
|

Structure and functional impact of seed region variant in MIR-499 gene family in bronchial asthma

Abstract: BackgroundSmall non-coding RNAs (microRNAs) have been evolved to master numerous cellular processes. Genetic variants within microRNA seed region might influence microRNA biogenesis and function. The study aimed at determining the role of microRNA-499 (MIR-499) gene family polymorphism as a marker for susceptibility and progression of bronchial asthma and to analyze the structural and functional impact of rs3746444 within the seed region.MethodsGenotyping for 192 participants (96 patients and 96 controls) in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 54 publications
0
28
0
Order By: Relevance
“…These results indicated that placental exosomes in early pregnancy may play a significant role in the maternal immune inflammatory process. Consistent with this hypothesis, miR-499 is reportedly involved in the immune inflammatory process 25 , suggesting that miR-499 may play a crucial role in maternal immune regulation during early pregnancy in dairy cows. To further investigate the differential abundance of placental exosomal bta-miR-499 in early pregnancy, we analyzed bta-miR-499 levels in exosomes isolated from the plasma of non-pregnant (G.D.0, n = 5) and early pregnant cows (G.D.60, n = 5).…”
Section: Resultsmentioning
confidence: 54%
“…These results indicated that placental exosomes in early pregnancy may play a significant role in the maternal immune inflammatory process. Consistent with this hypothesis, miR-499 is reportedly involved in the immune inflammatory process 25 , suggesting that miR-499 may play a crucial role in maternal immune regulation during early pregnancy in dairy cows. To further investigate the differential abundance of placental exosomal bta-miR-499 in early pregnancy, we analyzed bta-miR-499 levels in exosomes isolated from the plasma of non-pregnant (G.D.0, n = 5) and early pregnant cows (G.D.60, n = 5).…”
Section: Resultsmentioning
confidence: 54%
“…MiR-499 is also associated significantly with myocardial infarction, and together with miR-133a and miR-208a, they represent potential early diagnostic biomarkers of myocardial infarction [97][98][99][100]. Furthermore, miR-499 is significantly involved in the inflammatory signaling pathways of bronchial asthma [101]. No data on the role of miR-499a-5p in pathogenesis of endothelial dysfunction are currently available.…”
Section: Discussionmentioning
confidence: 99%
“…Another candidate miRNA in atopic asthma is miR-499. Toraih et al [ 50 ] demonstrated that a polymorphism (rs3746444), resulting in A>G substitution in the seed region of this miRNA gene, was associated with asthma risk in the population of Egyptian children and adults. The same polymorphism showed a significant association with spirometry results (increased forced expiratory volume in 1 s, FEV 1 ) in a population of Korean patients with AG/GG genotype in comparison to patients with AA genotype [ 51 ].…”
Section: Ncrna Studies In Asthmamentioning
confidence: 99%